100 kWe solar thermochemical pilot power plant: design, construction and testing. (February 2019) - Liu, Taixiu; Liu, Qibin; Bai, Zhang; Lei, Jing; Sui, Jun
Abstract: The engineering design, construction and testing of a 100 kWe solar-hybrid power generation pilot plant are conducted in this work. In the pilot plant, solar energy is upgraded to chemical energy of solar fuel (H2 and CO) by the solar thermochemical process of methanol decomposition reaction, and steadily stored and effectively utilized as the forms of chemical energy of solar fuel. The solar fuel is fed to the internal combustion engine to generate power. The solar generation pilot plant, including four solar thermochemistry units (with solar field area of 198 m 2 ), power generation unit (100 kWe ), syngas storage unit (with the volume of 19.2 m 3 ), preheating unit and measurement instrumentation, is built. The thermodynamic performances of the pilot plant are experimentally investigated, and the solar-to-chemical energy efficiency ranges from 37.12% to 45.51% when the solar flux is 404-761 W/m 2 .